On the Proverbial Conceptualization of the World - Baghdasaryan, Hasmik (Armenian Folia Anglistika, 2012)
The proverbial concept of the world has its unique place in the linguistic picture of the world. It is perceived as an unusual way of secondary conceptualization of the reflected reality expressed by proverbs and sayings that are characterized by binary reference. The first one is based on the material-perceptual cognition of the objective reality, whereas the second one is the result of human associative-symbolic thinking. Proverbs and sayings can be viewed as a form of worldview and world perception or as G. Gachev notes, they are the artistic logic and the mental “design” of a nation. Thus, proverbial meaning is anthropocentric, since it reflects the basic characteristics of human essence and human activity, but at the same time it is ethnocentric, in so far as it reflects the characteristic features of the given ethnos creating a certain type of culture, a certain national picture of the world. In the proverb stock of each language the general and national are harmoniously intertwined.